Gold Nanoclusters in Cancer Photothermal Therapy: Mechanisms, Theranostic Applications, and Clinical Translation Over the Last Decade (World Journal of Experimental Biosciences, 2025)
This last decade has seen the rise of gold nanoclusters (AuNCs) as a new, revolutionary class of photothermal agents for cancer therapy. The AuNCs (<2 nm) have a high surface area-to-volume ratio and exhibit efficient electron-to-phonon coupling. AuNCs possess favorable renal clearance properties due to their extremely small hydrodynamic diameters. This review article provides a structured summary of advancements made in the areas of AuNC synthesis, ligand-shell engineering, environmentally friendly fabrication methodologies, and large-scale manufacturing methods during the years of 2015-2025. It also focuses on the role atomic precision and surface chemistry play in the photothermal performance, biodistribution, protein corona formation, and nano–bio interactions of AuNCs; in addition, we highlight the mechanistic details associated with non-radiative relaxation pathways, energy gap modulation, and optimizing photothermal conversion efficiency. It also provides proof of concept that AuNCs are suitable as multifunctional theranostic platforms that integrate both fluorescence and photoacoustic imaging into combination strategies of chemo-photothermal and immune-photothermal therapy, with immune checkpoint blockade to elicit a systemic immune response against tumor cells. The study demonstrates rapid renal elimination and low accumulation of AuNCs over long-term duration, while addressing some of the historical concerns associated with traditional inorganic nanoparticles. Finally, the translational barriers facing AuNCs were highlighted, including regulatory standardization, reproducibility, and cost-effectiveness. The future with artificial intelligence (AI) will support AuNCs synthesis Thus, AuNC-based photothermal therapy is an exciting new advancement in nanomedicine and is predicted to be on a fast track for use in precision oncology from the lab through to integration into clinical practice by 2030.